Tuition fees and equality of university enrolment: The case of Ghana technology university college - Bentum Anita (knust, 2025)
A thesis submitted to the institute of distance learning, Kwame Nkrumah University of Science and Technology, in partial fulfilment of the requirements for the award of the degree of Master of science in Accounting and Finance